A survey on plant resource in home gardens in peninsular Malaysia / Mohd Raznan Ramli - Ramli, Mohd Raznan (2012)

(untitled)
This study was carried out to describe and characterize uses of plants that are tended or cultivated in home gardens in Peninsular Malaysia. A survey through floristic inspection of home gardens and semi-structured interviews with home garden owners were carried out at 94 home at various villages in Peninsular Malaysia from June through December of 2008. A total of 120 species of plants were encountered of which food plants namely Cocus nucifera L., Nephelium lappaceum L., Musa paradisiacal L., Durio zibethinus Murr and Mangifera indica L were found in most of the home gardens. Most of the species of plants encountered in this study were food plants (51.3%). This was followed by medicinal (17.1 %), ornamental (11.7 %), multiple uses (9.9 %), spice and flavor (7.2%), handicraft (1.8 %), and dye (0.9%).The most common plant family in term of the number of species was Leguminosae. This was followed by Zingiberaceae, Sapindaceae and Malvaceae . Market-based technique, good substitute approach and contingent valuation method are the suggested method to do valuate most of the plants species found in this study.